Erratum: COVID-19 Seroprevalence among Healthcare Workers in a University Hospital in Southeastern Turkey - Karslıgil, Tekin; Akdoğan, Hüseyin (European Journal of Therapeutics, 2021)
In the article by Karslıgil and Akdoğan, entitled “COVID-19 Seroprevalence among Healthcare Workers in a University Hospital in South-eastern Turkey” that was published in the June 2021 issue of the European Journal of Therapeutics (Eur J Ther; 27 (2): 106-112, DOI: 10.5152/eurjther.2021.20106), the authors declared that they erroneously forgot to add the financial support of the study and request-ed a correction. Author’s correction request were evaluated and accepted by the Editorial Board. Thus, the article has been corrected accordingly and updated in the journal’s archive. You may access the updated article via the link below. https://doi.org/10.5152/eurjther.2021.20106